Epidemic networks and potential sources of bacterial wilt infection in a potato seed network in Kenya - Gachamba, S.; Xing, Y.; Andersen, K.F.; Garrett, K.A.; Miano, D.W.; Mwang’ombe, A.W.; Sharma, K. (CAB International, 2022)
Potato seed systems in Kenya are largely informal, characterized by high seed degeneration due to the buildup of seed- and soil-borne diseases, including bacterial wilt caused by Ralstonia solanacearum. Informal sources of seed include neighbors, local markets and farmer-saved seed, and present a risk for spread and establishment of disease. To understand the larger context of potato disease risk in Kenya, we used network analysis to evaluate (1) epidemic risk through potato trade networks centered around East Africa, and (2) locations in East Africa likely to be particularly important for epidemic management because of their high potato cropland connectivity. We evaluated the interactions of the key stakeholders in a potato seed system and used network analysis to identify locations that are likely to be important for the spread of infection of R. solanacearum in a potato seed distribution network in Meru, Kenya. Household details, seed sources, quantities sold, pest incidence and management practices, knowledge about seed degeneration and farmers' sources of information on potato production were obtained and analyzed. The survey revealed that self-saved, neighbors, seed companies, friends, exchange, and markets are the main seed sources. Only 43% of total seed transacted was certified. Users of uncertified seeds have high disease risk, and this is an especially important risk if their roles in the network give them the potential to be 'superspreaders' of disease.